2021
DOI: 10.3389/fimmu.2021.757249
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon and the Spectrum of Susceptibility to Viral Infection and Autoimmune Disease: A Shared Genomic Signature

Abstract: Type I interferons (IFN-I) and their cognate receptor, the IFNAR1/2 heterodimer, are critical components of the innate immune system in humans. They have been widely explored in the context of viral infection and autoimmune disease where they play key roles in protection against infection or shaping disease pathogenesis. A false dichotomy has emerged in the study of IFN-I where interferons are thought of as either beneficial or pathogenic. This ‘good or bad’ viewpoint excludes more nuanced interpretations of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 98 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…In particular, the expression of type I IFN (IFN-β) was significantly upregulated by flagellin stimulation of RAW264.7 cells, which was verified by qRT-PCR. Type I IFN binds to the interferon α/β receptor and induces the expression of more than 300 ISGs through the Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway [ 43 ]. Our RNA-Seq analysis revealed that various ISGs were significantly upregulated in expression in FliC-treated RAW264.7 cells, including those encoding the myxovirus resistance proteins (Mx1 and Mx2), the IFIT family (IFIT1, IFIT2, and IFIT3b), and IRF3-dependent ISGs (ISG15, ISG20, OAS1b, etc).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the expression of type I IFN (IFN-β) was significantly upregulated by flagellin stimulation of RAW264.7 cells, which was verified by qRT-PCR. Type I IFN binds to the interferon α/β receptor and induces the expression of more than 300 ISGs through the Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway [ 43 ]. Our RNA-Seq analysis revealed that various ISGs were significantly upregulated in expression in FliC-treated RAW264.7 cells, including those encoding the myxovirus resistance proteins (Mx1 and Mx2), the IFIT family (IFIT1, IFIT2, and IFIT3b), and IRF3-dependent ISGs (ISG15, ISG20, OAS1b, etc).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of this outbreak, wherein all HCV-exposed individuals were pregnant females, potentially limits the extrapolation of findings from the cohort to other less homogenous groups. Several sex differences in the immune systems of males and females were described, including in Toll-like receptor (TLR) expression, the type I IFN system, and the ability to spontaneously resolve HCV infection [ 71 , 72 , 73 , 74 ]. Given the Irish anti-D cohort are all female, phenotypes described using data from these donors may not apply directly to HCV-exposed males.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathway regulators have also been shown to have variants causing IEI such as JAK1, TYK2, IFNAR1, and IFNAR2 [63][64][65]. While IEI have been thought to be rare, common single nucleotide polymorphisms (SNPs) have also been found in TYK2 and IFNAR1 and are associated with improved protection from infection as well as increased risk of autoimmunity [66]. The prevalence of such SNPs may account for a wide range of IFN pathway responses among individuals [67,68].…”
Section: Discussionmentioning
confidence: 99%